Comparison of in‐patient costs for children treated on the AAML0531 clinical trial: A report from the Children's Oncology Group. Issue 10 (6th May 2015) - Getz, Kelly D.; Li, Yimei; Alonzo, Todd A.; Hall, Matthew; Gerbing, Robert B.; Sung, Lillian; Huang, Yuan‐Shung; Arnold, Staci; Seif, Alix E.; Miller, Tamara P.; Bagatell, Rochelle; Fisher, Brian T.; et al.
<x xml:space="preserve">Abstract</x> Background A better understanding of drivers of treatment costs may help identify effective cost containment strategies and prioritize resources. We aimed to develop a method for estimating inpatient costs for pediatric patients with acute myeloid leukemia (AML) enrolled on NCI‐funded Phase III trials, compare costs between AAML0531 treatment arms (standard chemotherapy ± gemtuzumab ozogamicin (GMTZ)), and evaluate primary drivers of costs for newly diagnosed pediatric AML. Procedure Patients from the AAML0531 trial were matched on hospital, sex, and dates of birth and diagnosis to the Pediatric Health Information Systems (PHIS) database to obtain daily billing data. Inpatient treatment costs were calculated as adjusted charges multiplied by hospital‐specific cost‐to‐charge ratios. Generalized linear models were used to compare costs between treatment arms and courses, and by patient characteristics. Results Inpatient costs did not differ by randomized treatment arm. Costs varied by course with stem cell transplant being most expensive, followed by Intensification II (cytarabine/mitoxantrone) and Induction I (cytarabine/daunorubicin/etoposide). Room/board and pharmacy were the largest contributors to inpatient treatment cost, representing 74% of the total cost. Higher AML risk group (P = 0.0003) and older age (P < 0.0001) were associated with significantly higher daily inpatient cost. Conclusions Costs from external data sources can be successfully integrated into NCI‐funded Phase III clinical trials. Inpatient treatment costs did not differ by GMTZ exposure but varied by chemotherapy course. Variation in cost by course was driven by differences in duration of hospitalization through room/board charges as well as increased clinical and pharmacy charges in specific courses. Pediatr Blood Cancer 2015;62:1775–1781. © 2015 Wiley Periodicals, Inc.